2010
DOI: 10.1021/ct900440t
|View full text |Cite
|
Sign up to set email alerts
|

An RNA Molecular Switch: Intrinsic Flexibility of 23S rRNA Helices 40 and 68 5′-UAA/5′-GAN Internal Loops Studied by Molecular Dynamics Methods

Abstract: Functional RNA molecules such as ribosomal RNAs frequently contain highly conserved internal loops with a 5’-UAA/5’-GAN (UAA/GAN) consensus sequence. The UAA/GAN internal loops adopt distinctive structure inconsistent with secondary structure predictions. The structure has a narrow major groove and forms a trans Hoogsteen/Sugar edge (tHS) A/G base pair followed by an unpaired stacked adenine, a trans Watson-Crick/Hoogsteen (tWH) U/A base pair and finally by a bulged nucleotide (N). The structure is further sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 93 publications
3
37
0
Order By: Relevance
“…This method has been successfully applied to a number of biological processes of similar complexity. 51,52 We have used the NEB approach to model the pathway for cholesterol transfer between the NPC1(NTD) and NPC2 Figure 9, discussed in more detail in the text. The colors of the arrows match the colors of the cholesterol molecule in the images shown in Figure 9 for different steps of the transfer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This method has been successfully applied to a number of biological processes of similar complexity. 51,52 We have used the NEB approach to model the pathway for cholesterol transfer between the NPC1(NTD) and NPC2 Figure 9, discussed in more detail in the text. The colors of the arrows match the colors of the cholesterol molecule in the images shown in Figure 9 for different steps of the transfer.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The parm99 and parmbsc0 force fields appear to provide equivalent (within the limits of the sampling achieved in our work) description of most parts of the present system, in agreement with other recent tests. 62,63 The parmbsc0 obviously penalizes the γ-trans backbone substates. This, however, usually does not have a substantial effect on the RNA behavior, and we cannot make any recommendation which of the two force fields is closer to reality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the force field variants parm94, parm99, and parmbsc0 all resulted in overall similar descriptions of RNA structures in simulations of up to 100 ns length in previous studies. 54,55 Thus, we expect that the main results of our simulations will not be sensitive to the used Amber force field variant.…”
Section: Methodsmentioning
confidence: 99%
“…50,51 A recent reparameterization of the R and γ torsions in these force fields led to the parmbsc0 force field, 52 which improved the simulation of DNA duplexes on very long time scales (1 µs range). However, further tests on A-RNA duplexes 53 and UAA/GAN internal loops of 23S rRNA H40 54 revealed that the penalization of the R/γ transitions in the parmbsc0 force field may be too excessive for RNA structures and leads to a modest narrowing of the major groove due to the suppression of the γ-trans states. 54 In the present study, when investigating R and γ torsions sampled during MD and REMD simulations using parm94, we found only one to two transitions toward R/γ t/t substates, e.g., for nucleotides 20 and 28 in the two stem regions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation